P5-S5.03 Partner notification and treatment for maternal syphilis in Lima, Peru: knowledge, attitudes, and practices of health providers and patients. (10th July 2011) - Williams, B; Garcia, P; Carcamo, C; Guiterrez, M Chiape; De la Rosa Roca, S; Calderon, M V; Peeling, R
Abstract : We sought to identify factors that affect partner notification and treatment for maternal syphilis as part of an implementation research study on the feasibility of using rapid syphilis testing (RST) in reproductive health services in Lima, Peru. Congenital syphilis remains a significant problem in many regions of the world. Prevention depends on successful treatment of syphilis-positive pregnant women. Treatment of sexual partners is essential to prevent re-infection. We conducted exploratory research to identify factors that contributed to poor rates of partner treatment after month 3 of RST implementation. Quantitative data collected from 127 RST-positive pregnant women was used to identify patient factors associated with partner treatment. A subset of 18 women participated in qualitative interviews. Fifty-eight health providers completed a survey of knowledge, attitudes, and practices related to counselling and treatment of syphilis-positive women and partners. National guidelines for follow-up and treatment of syphilis were also reviewed. Providers reported lack of human resources and coordination as reasons for failure to perform follow-up of partners. 33 (56.9%) providers said they were not well prepared for counselling and would like additional training. Providers relayed strategies they used to treat partners, and reported paying greater attention to follow-up of partners and documentation of partner treatment since RST introduction. Fear of blame, violence, and abandonment were cited as reasons why women were less likely to notify a partner, while distrust in test results, "machismo", and lack of knowledge were said to make partners less likely to seek treatment. Women interviewed who had notified partners of their diagnosis reported that notification was easier when a health provider was present. No women reported violent responses from their partners after notifying. Reasons women said that partners had not received treatment included difficulty seeking care during regular clinic hours and lack of knowledge. In bivariate analysis only marital status was found to predict whether or not partners received treatment (p=0.004) see Abstract P5-S5.03 table 1 . Data collected from patients and providers showed that women were aware of the importance of partner notification, but male partners often did not seek treatment due to systemic barriers. Health systems should prioritise partner-friendly treatment strategies. National guidelines need to clearly define procedures for partner follow-up.